A clinical audit of the process of care for women with gestational diabetes mellitus in a Malaysian public polyclinic - Hassan, Faezah; Ching, Siew Mooi; Ling, Poh Cheng; Jaffar, Nurhidayah; Lee, Kai Wei (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Proper gestational diabetes mellitus (GDM) care is essential for optimal control and thus prevents ad-verse perinatal outcomes. This audit aimed to determine the quality of GDM care provided by a public polyclinic. Methods: The audit was performed on the clinic-based medical record of GDM patients who had undergone at least three prenatal follow-ups and one postnatal follow-up between January and November 2012. Patients with pre-existing diabetes mellitus were excluded. Results: A total of 74 medical records were audited and it showed that 94.6% of patients were of age 25 and above, 91.9% were Malays, 71.6% were multigravida and 98.6% had risk factors of GDM. 54.1% of diagnoses were made during the second trimester, while 25.7% and 20.2% of cases were detected during the first and third trimester respectively. All of the GDM patients had their weight and blood pressure monitored, 85.1% had their fundal height checked as scheduled and 85.1% were referred for diet counselling. 81.9% and 100% of GDM patients who were not on treatment and on treatment correspondingly had their blood sugar profile monitoring done as recommended. Only 13.5% of GDM patients were given prenatal family planning counselling and 35.1% were given a six weeks’ postnatal oral glucose tolerance test appointment. Monthly ultrasound screening and HbA1c monitoring was done in merely 51.4% and 58.1% of the GDM patients respectively. Conclusion: The GDM care process in this public polyclinic could be improved further to achieve the standard recommendations.